The emergence of Brucella canis as a public health threat in Europe: what we know and what we need to learn - Vitomir Djokic; Luca Freddi; Fabrizio de Massis; Elina Lahti; Marielle H. van den Esker; Adrian Whatmore; Anna Haughey; Ana Cristina Ferreira; Giuliano Garofolo; Falk Melzer; Flavio Sacchini; Ad Koets; et al. (Emerging Microbes and Infections, 2023)
The zoonotic bacteria, Brucella canis, is becoming the leading cause of canine brucellosis in Europe. In dogs, it causes reproductive problems as well as non-specific lameness or discospondilitis. In humans, B. canis can be origin of chronic debilitating conditions characteristic to its genus such as undulant fever, splenomegaly, and lymphadenopathy. Although B. canis shows some pathogenic characteristics similar to B. abortus and B. melitensis, it lacks surface O-polysaccharide, like nonzoonotic B. ovis. This review shows that host–B. canis interactions are still poorly understood, with many knowledge and capability gaps, causing relatively poor sensitivity and specificity of existing diagnostic tools. Currently, there is no vaccine for this rough Brucella species. Besides, antimicrobial therapy does not guarantee bacterial elimination, and infection relapses are frequently reported, increasing the risks of antibiotic resistance development. B. canis has been detected in dogs in almost all European countries which increased human exposure, but currently there is no systematic surveillance. Moreover, B. canis caused brucellosis is not included in Animal Health Law, and therefore there is no legal framework to tackle this emerging infectious disease. To map out the diagnostic strategies, identify risks for human infections and propose management scheme for infected pet and kennel dogs, we present current understanding of canine B. canis caused brucellosis, outline major knowledge gaps and propose future steps. To address and highlight challenges veterinary and public health services encounter in Europe, we developed two B. canis infection scenarios: of a single household pet and of a kennel dog in larger group.